2013
DOI: 10.1002/app.39303
|View full text |Cite
|
Sign up to set email alerts
|

Novel phenyl‐POSS/polyurethane aqueous dispersions and their hybrid coatings

Abstract: A facile and rapid preparation of 3-(2-aminoethylamino)propylheptaphenylPOSS (AA-POSS), a special phenyl-POSS that contains two functional amino groups (Scheme 1), is demonstrated by the corner-capping method. Then AA-POSS forms a series of novel phenyl-POSS=PU aqueous dispersions. The structure of AA-POSS has been confirmed by Si NMR, and ESI-MS. The POSS=PU hybrid films are studied by Fourier transform infrared spectrometer (FT-IR), gel permeation chromatography (GPC), scanning electron microscope (SEM), X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
(57 reference statements)
1
6
0
Order By: Relevance
“…Figure shows the XRD pattern of the samples PU‐1 to PU‐7. It reveals that there is a 2θ diffraction peak at approximately 20°, which is in reasonable agreement with the reported value of PU elsewhere . The intensity of this peak gradually decreases from samples PU‐1 to PU‐5, followed by a reverse increase from PU‐6 to PU‐7.…”
Section: Resultssupporting
confidence: 90%
“…Figure shows the XRD pattern of the samples PU‐1 to PU‐7. It reveals that there is a 2θ diffraction peak at approximately 20°, which is in reasonable agreement with the reported value of PU elsewhere . The intensity of this peak gradually decreases from samples PU‐1 to PU‐5, followed by a reverse increase from PU‐6 to PU‐7.…”
Section: Resultssupporting
confidence: 90%
“…That from 250 to 400°C could be attributed to the dissociation of urethane bonds to form isocyanates, alcohol, and amines. The decomposition above 400°C was mainly due to the dissociation of the soft segments in the polyurethane and POSS cage structure . As the POSS content increased, the first decomposition temperature was slightly increased, and the second decomposition temperature obviously increased, which meant that the POSS particles were good to the thermal stability of the polyurethane.…”
Section: Resultsmentioning
confidence: 99%
“…[29][30][31] Various substituents were introduced to the three silanole groups at the opening moiety ["X" in Chart 1(b)], and the composite films of PMMA with the synthesized IC-POSS fillers were fabricated. Herein, we have demonstrated that IC-POSS fillers are effectively dispersed in a PMMA matrix.…”
Section: Introductionmentioning
confidence: 99%